Pengalaman ners dalam upaya mengendalikan covid-19 - Yeni Rusyani; Putri Kusumawati Priyono (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Covid-19 still a serious problem in th world. Nurses are someone who has the most contact with patients who are at risk of contracting the Covid-19 virus. The majority of nurses, with large numbers in health care centers, are directly involved and in contact with patients for 24 hours. Objective: To identify the experience of nurses while providing health services to patients infected with Covid-19. Methodes: Qualitative data obtained through in-depth interviews with seven nurses from several hospitals in Yogyakarta. Results: The are four main themes, namely knowledge about how to treat covid 19 patients, motivation to care for patients, psychological conditions of nurses while caring for covid 19 patients, efforts to reduce the risk of contracting and the role of nurses in providing health services to families of covid 19 patients. Conclution: Most of the participants heard information about Covid-19, from information media such as the, television, and webinars boldly. Have knowledge about the treatment of Covid-19 disease. Good motivation can influence nurses in service to patients. Circumstances such as anxiety and fear of contracting a problem that must be overcome and family involvement is still very minimal so that it needs to be followed up.